A front-end amplifier with tunable bandwidth and high value pseudo resistor for neural recording implants. (January 2022) - Ashayeri, Mehdi; Yavari, Mohammad
Abstract: In this paper, a tunable front-end amplifier is presented for neural recording implants. To program the low cut-off frequency, a bias circuit is used to adjust the value of pseudo resistors with lower sensitivity to the process variations and also to achieve very large value about 1 TΩ with high linearity. The band pass filter (BPF) can adjust high cut-off frequency and power consumption with two recording modes. The high cut-off frequency is 4.15 kHz and 8.2 kHz in low recording (LR) and high recording (HR) modes, respectively. The low cut-off frequency can be adjusted to 0.8 Hz and 300 Hz. The proposed amplifier is able to separate the neural signals with different frequencies for amplification. It has been designed and simulated in TSMC 0.18 μm CMOS process. The achieved input-referred noise is about 2.1 μVrms and 1.7 μVrms in HR and LR modes, respectively. The total power consumption is 3.6 μW from a 1-V supply with −46.3 dB THD.